2004
DOI: 10.1002/cphc.200301058
|View full text |Cite
|
Sign up to set email alerts
|

Backbone‐Only Protein Solution Structures with a Combination of Classical and Paramagnetism‐Based Constraints: A Method that Can Be Scaled to Large Molecules

Abstract: Herein, it is shown that a medium-resolution solution structure of a protein can be obtained with the sole assignment of the protein backbone and backbone-related constriants if a derivative with a firmly bound paramagnetic metal is available. The proof-of-concept is provided on calbindin D9k, a calcium binding protein in which one of the two calcium ions can be selectively substituted by a paramagnetic lanthanide ion. The constraints used are HN (and Ha) nuclear Overhauser effects (NOEs), hydrogen bonds, dihe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…It was also shown that paramagnetism-based restraints, together with identification of the secondary structure elements, may provide the backbone solution structure of a metalloprotein even in the absence of any NOEs. [64,94,108] In conclusion, paramagnetism-based restraints have been proven to be precious for the solution structure determination of paramagnetic proteins. This is particularly true if, for any reason, the number of NOEs is limited.…”
Section: Residual Dipolar Couplingsmentioning
confidence: 98%
See 3 more Smart Citations
“…It was also shown that paramagnetism-based restraints, together with identification of the secondary structure elements, may provide the backbone solution structure of a metalloprotein even in the absence of any NOEs. [64,94,108] In conclusion, paramagnetism-based restraints have been proven to be precious for the solution structure determination of paramagnetic proteins. This is particularly true if, for any reason, the number of NOEs is limited.…”
Section: Residual Dipolar Couplingsmentioning
confidence: 98%
“…However, it was shown that the d pcs values are absolutely consistent with NOEs and dihedral-angle structural restraints. [60][61][62] A protocol has been thus implemented to include these restraints in the most popular software packages for solution structure determination, such as DYANA/ CYANA [63,64] and Xplor-NIH. [65] Although such programs are not optimized for handling these restraints, due to the complicated form of the energy surface, they have been shown to be precious not only for protein refinement but also for ab initio structural calculations.…”
Section: Hyperfine Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…1) were used (47). ¶ Such calculations also show that some distance restraints are always needed, otherwise pcs alone hardly converge to a correct folding (22,48).…”
Section: Fig 2 13 C Pcs Observed (Blue Lines) For Fully Labeled Commentioning
confidence: 99%